P267 What do gastroenterology professionals call gastrointestinal (GI) problems after pelvic radiotherapy?. (19th June 2022) - Smith, Lesley; Sacks, Benjamin; Steele, Sarah; Andreyev, Jervoise
Abstract : Introduction: A standard terminology is required for the chronic symptoms that may occur after pelvic radiotherapy (RT) as this will ensure that patients are treated not only for GI symptoms but are also referred when required for bladder and sexual problems, pain, nerve/bone/vascular damage, lymphoedema and mental health. ICD coding indicates radiation proctitis/colitis should be standard terms - however the '-itis' suffix indicates localised inflammation and fails to acknowledge the complex co-existing ischaemic and fibrotic pathology of radiation-induced damage which is mainly submucosal. Methods: The Pelvic Radiation Disease Association polled visitors to the BSG2019 exhibition by showing them a choice of answers to "What do you call GI symptoms caused by pelvic radiotherapy?". Results: Respondents (n=164) were physicians (61%), nurses and other professions (39%). The majority diagnosed GI disorders after pelvic radiotherapy. Many chose more than one response ( Table 1 ). Radiation proctitis, enteritis and colitis were the most commonly chosen. 37 respondents chose 'Pelvic Radiation Disease' and 30 chose 'radiation enteropathy'. Conclusions: The terminology for radiation damage is not standardised. This may impact on investigation and treatment choices by clinicians, and provides no incentive to address the spectrum of issues that may arise, and which seriously impact on quality of life. Chronic GI problems after pelvic radiotherapy are increasingly prevalent so gastroenterologists may see more of these patients than other specialists. The term 'Pelvic Radiation Disease' was coined 1 so that radiation-induced chronic toxicity is seen as a disease, rather than a constellation of vague and poorly defined symptoms. Use of this term allows prevalence to be measured, a holistic approach to be developed towards patients, a better definition of optimal therapy 2 and facilitation of research. Further work and debate are needed to reach consensus on this issue. References: 1. Andreyev HJN et al. Defining pelvic-radiation disease for the survivorship era. Lancet Oncology. 2010;11(4):310-2. 2. Andreyev HJN et al. The practical management of the gastrointestinal symptoms of pelvic radiation disease. Frontline Gastroenterol 2015;6(1):53-72.